KRITIK DIKOTOMI TASAWUF SUNNI DAN TASAWUF FALSAFI AHMAD SIRHINDI - Muhammad Arif (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Though the coming of some tasawuf schools is unavoidable, the dichotomy of these schools namely sunni and falsafi is somehow too far. This dichotomy is at its turn will declare that tasawuf sunni is in the correct path of shari’a, while tasawuf falsafi is not. One of the ambitious sufi’s Imam who made this dichotomy popular is Ahmad Sirhindi. The systematic critic of Ahmad Sirhindi towards tasawuf falsafi gives big impact in the future to the spreading of this binary view. Therefore, to review this problematic classification of tasawuf, the reinterpretation of Ahmad Sirhindi’s argument is needed. This article will explain the dichotomy of tasawuf based on the view of Ahmad Sirhindi and the critical comments on this idea.